Estimating the use of biological samples in Finnish biobanks and hospital collections - Tupasela, Aaro; Southerington, Tom; Mäkelä, Johanna; Kallio, Lila; Perälä, Merja; Kosma, Veli-Matti; Mannermaa, Arto; Jokela, Tiina; Pitkänen, Kimmo; Kontro, Mika; Vesterinen, Tiina; Punkka, Eero; et al. (Springer Science and Business Media LLC, 2025)
Finland has steadily developed its biobanking infrastructures since the early 2010s. This article presents a systematic overview of the number of biological samples that have been provided for research since 2013 when the Finnish Biobank Act came into force. Using data from individual biobanks and from permits issued by Fimea (formerly Valvira), we present the most up-to-date and complete account of sample use at a national level. Between 2014 and 2023 a total of 1,474,881 samples were provided through 998 sample requests. A better understanding of the use of biological samples at the national level can help highlight the important impact biobanking has as an infrastructure for supporting research. We argue that developing standards can help in developing national biobanking strategies and identify areas where biobanking can be further developed. We also conclude that the ability to combine tissue samples and health data flexibly and efficiently is essential and needs to be secured also within the context of the European Health Data Space (EHDS).